Use of Isoniazid Preventive Therapy for Tuberculosis Prophylaxis Among People Living With HIV/AIDS: A Review of the Literature. (15th April 2015) - Briggs, Melissa A.; Emerson, Courtney; Modi, Surbhi; Taylor, Nicholas Kenji; Date, Anand
Abstract : Background: Tuberculosis (TB) is the leading preventable cause of death in persons living with HIV (PLHIV), accounting for over a quarter of all HIV-associated deaths in 2012. Isoniazid preventive therapy (IPT) has the potential to decrease TB-related cases and deaths in PLHIV; however, implementation of this has been slow in many high HIV- and TB-burden settings. Methodology: We performed an assessment of the evidence for the use of IPT in adults living with HIV based on a review of the literature published from 1995 to 2013. Eligible articles included data on mortality, morbidity, or retention in care related to the provision of IPT to adults with HIV in low- or middle-income countries. Cost-effectiveness information was also abstracted. Results: We identified 41 articles involving over 45, 000 PLHIV. While there was little evidence to demonstrate that IPT reduced mortality in PLHIV, there was substantial evidence that IPT reduced TB incidence. While these findings were consistent irrespective of CD4 or antiretroviral therapy status, studies frequently demonstrated a greater benefit among patients with a positive TB skin test (TST). Duration of effectiveness and benefits of prolonged therapy varied across settings. Conclusions: This analysis supports World Health Organization recommendations for the provision of IPT to PLHIV to reduce TB-associated morbidity and serves to highlight the need to strengthen IPT implementation. While there appears to be a greater benefit of IPT among PLHIV who are TST positive, IPT should be provided to all PLHIV without presumptive TB when TST is not available. Abstract : Supplemental Digital Content is Available in the Text.